Parathyroid hormone secreting metaplastic breast carcinoma: a case report of paraneoplastic syndrome - Al-Qaraghuli, Ahmed Mohammed Saliem; Nor Faezan AR,; Rohaizak Muhammad, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Paraneoplastic syndrome (PNS) is a distant neurological manifestation of an underlying tumour. Humoral hypercalcaemia of malignancy is a form of paraneoplastic syndrome where there is an increased in calcium levels. In this article we report a 48 year old lady, with no known medical illness and presented with symptomatic hypercalcaemia. She presented to our institution complaining of a fungating and ulcerating mass over the right breast, measuring 11 X 15 cm and associated with gradual paraxial body weakness. Further investigations revealed the lesion to be an invasive breast carcinoma with metaplastic features. Computed tomography (CT) scan showed a locally advanced breast carcinoma with right axillary node metastasis, without evidence of distant metastasis. Serum calcium, i-PTH together with SPECT has confirmed the patient to have a humoral hypercalcaemia malignancy with elevated ectopic parathyroid hormone level. Bone scan did not reveal any evidence of metastasis. High volume intake and loop diuretics were employed in the management of hypercalcaemia, which was eventually resolved following mastectomy with axillary clearance of the ipsilateral side. Currently she’s she is under oncologist’s follow up for further management.